ERUPTIVE HISTORY AND GEOCHRONOLOGY OF MOUNT MAZAMA AND THE CRATER LAKE REGION, OREGON - Bacon C.R.; Lanphere M.A. (My University, 2006)
Geologic mapping, K-Ar, and 40Ar/39Ar age determinations, supplemented by paleomagnetic measurements and geochemical data, are used to quantify the Quaternary volcanic history of the Crater Lake region in order to define processes and conditions that led to voluminous explosive eruptions. The Cascade arc volcano known as Mount Mazama collapsed during its climactic eruption of ~50 km3 of mainly rhyodacitic magma ~7700 yr ago to form Crater Lake caldera. The Mazama edifice was constructed on a Pleistocene silicic lava field, amidst monogenetic and shield volcanoes ranging from basalt to andesite similar to parental magmas for Mount Mazama. Between 420ka and 35 ka, Mazama produced medium-K andesite and dacite in 2:1 proportion. The edifice was built in many episodes; some of the more voluminous occurred approximately coeval with volcanic pulses in the surrounding region, and some were possibly related to deglaciation following marine oxygen isotope stages (MIS) 12, 10, 8, 6, 5.2, and 2. Magmas as evolved as dacite erupted many times, commonly associated with or following voluminous andesite effusion. Establishment of the climactic magma chamber was under way when the first preclimactic rhyodacites vented ca.27 ka. The silicic melt volume then grew incrementally at an average rate of 2.5 km3 k.y.-1 for nearly 20 k.y. The climactic eruption exhausted the rhyodacitic magma and brought up crystal-rich andesitic magma, mafic cumulate mush, and wall-rock granodiorite. Postcaldera volcanism produced 4 km3 of andesite during the first 200-500 yr after collapse, followed at ca. 4800 yr B.P. by 0.07 km3 of rhyodacite. The average eruption rate for all Mazama products was ~0.4 km3 k.y.-1, but major edifice construction episodes had rates of ~0.8 km3 k.y.-1. The long-term eruption rate for regional monogenetic and shield volcanoes was ~0.07 km3 k.y.-1, but only ~0.02 km3 k.y.-1 when the two major shields are excluded. Plutonic xenoliths and evidence for crystallization differentiation imply that the amount of magma intruded beneath Mount Mazama is several times that which has been erupted. The eruptive and intrusive history reflects competition between (1) crystallization driven by degassing and hydrothermal cooling and (2) thermal input from a regional magma flux focused at Mazama. Before ca. 30 ka, relatively small volumes of nonerupted derivative magma crystallized to form a composite pluton because the upper crust had not been heated sufficiently to sustain voluminous convecting crystal-poor melt. Subsequently, and perhaps not coincidentally, during MIS 2, a large volume of eruptible silicic magma accumulated in the climactic chamber, probably because of heating associated with mantle input to the roots of the system as suggested by eruption of unusually primitive magnesian basaltic andesite and tholeiite west of Mazama. © 2006 Geological Society of America.
Keywords: ARC VOLCANISM; ARGON; CALDERAS; CRATER LAKE; GEOCHRONOLOGY; MOUNT MAZAMA; VOLCANOLOGY; Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен